2016
DOI: 10.1111/jop.12488
|View full text |Cite
|
Sign up to set email alerts
|

The role of hypoxia in oral cancer and potentially malignant disorders: a review

Abstract: Oral and oropharyngeal cancer are major health problems globally with over 500 000 new cases diagnosed annually. Despite the fact that oral cancer is a preventable disease and has the potential for early detection, the overall survival rate remains at around 50%. Most oral cancer cases are preceded by a group of clinical lesions designated 'potentially malignant disorders'. It is difficult to predict if and when these lesions may transform to malignancy, and in turn it is difficult to agree on appropriate mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…22 Hypoxia exists in many solid tumor microenvironments. 23 In these tumor cells, hypoxia condition induced the increase of HIF-1α level, and thus regulated the expression of downstream genes, which led to the change of cell progression. 24,25 Previous evidence has revealed that propofol is capable of reversing the effect of hypoxia on cell growth.…”
Section: Discussionmentioning
confidence: 97%
“…22 Hypoxia exists in many solid tumor microenvironments. 23 In these tumor cells, hypoxia condition induced the increase of HIF-1α level, and thus regulated the expression of downstream genes, which led to the change of cell progression. 24,25 Previous evidence has revealed that propofol is capable of reversing the effect of hypoxia on cell growth.…”
Section: Discussionmentioning
confidence: 97%
“…As a common feature of solid tumors, hypoxia causes oxidative stress and results in a redox imbalance in the tumor microenvironment ( 26 ). Some researchers have reported that the dysfunction and deregulation of hypoxia-related proteins are often an early event during oral carcinogenesis ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia plays a critical role in oral cancers, pharyngeal cancers, and OPMD [ 118 ]. Cells under conditions of hypoxic stress may present many responses including increased angiogenic capacity, metabolic changes, and modified growth and survival of cells.…”
Section: What Are the Main Chemically Carcinogenic Substances Of Bmentioning
confidence: 99%
“…Risk factors (e.g., alcohol, BQ, and cigarette) use may activate the transcription of hypoxia responsive genes. HIF1- α is the major regulator of cellular responses to hypoxia [ 118 ]. The energy metabolism reprogramming and destruction of evading immune are emerging aspects of cancer that are significantly controlled by hypoxia-induced genes that mediate tumor angiogenesis, vascularization, invasion, metastasis, and drug resistance [ 118 , 120 ].…”
Section: What Are the Main Chemically Carcinogenic Substances Of Bmentioning
confidence: 99%
See 1 more Smart Citation